Answer:
![(1)/(4x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/8c07o233wu6os87aaepznl2a497l0nlpco.png)
Explanation:
The negative exponential can be represented with the help of fractions. By this way, we also make the negative exponential disappear. For example, we can write:
![a^(-1) = (1)/(a)](https://img.qammunity.org/2020/formulas/mathematics/high-school/q4wveqienp6kgtr5jy754rs80da1jmnfmb.png)
The explanation is this:
Since
![a^(0)=1, (1)/(a)=(a^(0) )/(a^(1) ) = a^(0-1) =a^(-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/t0aq7l4rejeykly9fmis91qqurlk8e3vg8.png)
According to this definition, we can simplify our problem in the following way:
![(4x)^(-1) = (1)/((4x)^(1) ) = (1)/(4x)](https://img.qammunity.org/2020/formulas/mathematics/high-school/svjwku8osu7qfl452o0zu747z1h4esr5ym.png)